Earth : (Pearson, 2009)
Earth is a very small part of a vast universe, but it is our home. It provides the resources that support our modern society and the ingredients necessary to maintain life. Knowledge of our physical environment is critical to our well-being and vital to our survival. A basic geology course can help a person gain such an understanding. It can also take advantage of the interest and curiosity many of us have about our planet--its landscapes and the processes that create and alter them. The eleventh edition of Earth: An Introduction to Physical Geology, like its predecessors, is a college-level text that is intended to be a meaningful, non-technical survey for students taking their first course in geology. In addition to being informative and up-to-date, a major goal of Earth is to meet the need of students for a readable and user-friendly text, a book that is a highly usable "tool" for learning the basic principles and concepts of geology